Gender Representation in Sports Photography - Juliet, Ebube (International Journal of Arts, Recreation and Sports, 2024)
Purpose: The general objective of this study was to investigate gender representation in sports photography. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive’s time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to gender representation in sports photography. Preliminary empirical review revealed significant disparities, showing that male athletes were favored in terms of coverage and portrayal, with emphasis on their athleticism and competitiveness, while female athletes were underrepresented and often depicted based on their appearance and personal lives. This marginalization of women’s sports contributed to reduced sponsorship opportunities and public support, reinforcing traditional gender norms. The findings highlighted the need for equitable sports photography that accurately reflects female athletes' achievements to promote gender equality and inspire future generations, calling for efforts from media organizations, sports leagues, athletes, and educators. Unique Contribution to Theory, Practice and Policy: The Social Role Theory, Cultivation Theory and Framing Theory may be used to anchor future studies on gender representation in sports photography. The study recommended expanding theories like Social Role Theory, training media professionals to recognize and counteract biases, and implementing editorial guidelines for balanced coverage. Policy suggestions included regulatory frameworks for equal media coverage and incorporating gender equality into media rights agreements. The study also emphasized the need for educational initiatives to raise awareness and collaborations between industry stakeholders. Ongoing research and monitoring were suggested to track progress and ensure sustained efforts towards equitable gender representation.